الصحة التنظيمية وعلاقتها بالمواطنة التنظيمية لدي العامل بالمؤسسة الجزائرية - عيواز, نور الدين (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: 1- باللغة العربية هدفت هذه الدراسة إلى الكشف عن علاقة الصحة التنظيمية بالمواطنة التنظيمية لدي العاملين في مؤسسة الصندوق الوطني للضمان الاجتماعي بفروعه الثلاثة بمدينة المسيلة، وفي سبيل تحقيق أغراض الدراسة تم الاعتماد على المنهج الوصفي، الملاحظة المباشرة وأداة الاستبيان لجمع البيانات، التي تكونت من(63) سؤالا توزعت بين متغيرات الدراسة بأبعادها المعتمدة، وقد استخدم الباحث طريقة المسح الشامل لمجتمع الدراسة المتمثل في العاملين بالمؤسسة ميدان الدراسة البالغ عددهم(172) مفردة بحثية، وأظهرت الدراسة العديد من النتائج نذكر: • أن المؤسسة ميدان الدراسة تمتلك عنصر القيادة التحويلية الذي يتمتع بالكفاءة المهنية في مجال العمل. • أن المؤسسة ميدان الدراسة تعتمد على سياسة واضحة المعالم مع موردها البشري( كسياسة، التشجيع، التحفيز، التفويض، الحث اللفظي، الاتصال المباشر والمفتوح...الخ). • أن المؤسسة ميدان الدراسة تعتمد على أسلوب فريق العمل كآلية لتحقيق أهدافها. • أن المؤسسة ميدان الدراسة تعتمد في تمكين موردها البشري وظيفيا وسلوكيا من خلال أسلوب تنظيم الدورات التكوينية والتدريبية، إشراك العاملين، الشورى، التفويض للمسؤوليات، منظومة منح الحوافز) • وجود سلوكيات المواطنة التنظيمية بالمؤسسة ميدان الدراسة( سلوك الإيثار، وعي الضمير، السلوك الحضاري). • جاء رأي المرؤوسين بالغالبية حول طبيعة المعاملة التي ينتهجها الرئيس معهم أثناء انجاز مهامهم الوظيفية بالمنظمة، بأنها معاملته جيدة. • جاء رأي المرؤوسين بالغالبية حول تقييمهم لسياسة وأنظمة العمل بالمؤسسة ميدان الدراسة، على أنها سياسة وأنظمة عمل جيدة. • وجود علاقة بين الصحة التنظيمية والمواطنة التنظيمية كمفاهيم أساسية في هذه الدراسة الميدانية. • وجود علاقة بين القيادة التحويلية والمواطنة التنظيمية. • وجود علاقة بين فرق العمل الفعالة والمواطنة التنظيمية. • وجود علاقة بين التمكين الوظيفي للعاملين والمواطنة التنظيمية. Summary of the Study 1. In English This study aims to reveal the relationship of organizational health with organizational citizenship among employees of the National Fund for Social Security in its three branches in the city of M'sila. They were distributed among the study variables with their approved dimensions. The researcher used the method of a comprehensive survey of the study community represented by the employees of the institution in the field of study, which numbered (172) research subjects, and the study showed many results, the most important of which are: • That the institution in the field of study possesses a transformational leadership element that enjoys professional competence in the field of work. • That the institution, the field of study, relies on a well-defined policy with its human resource (such as policy, encouragement, motivation, delegation, verbal exhortation, direct and open communication...etc). • The institution, the field of study, relies on the work team method as a mechanism to achieve its goals. • That the institution, the field of study, relies on empowering its human resource functionally and behaviorally through the method of organizing training and training courses, involving employees, consultation, delegation of responsibilities, and a system of granting incentives. • The presence of organizational citizenship behaviors in the institution, the field of study (altruistic behavior, conscience awareness, civilized behavior). • The opinion of the subordinates came by the majority about the nature of the treatment pursued by the president with them during the completion of their job duties in the organization, as good treatment. • he opinion of the subordinates came in the majority about their evaluation of the organization's work policy and systems in the field of study, as good work policy and systems. • The existence of a relationship between organizational health and organizational citizenship as basic concepts in this field study. • There is a relationship between transformational leadership and organizational citizenship. • The existence of a relationship between effective work teams and organizational citizenship • There is a relationship between job empowerment of employees and organizational citizenship.
دراسة ميدانية بمؤسسة الصندوق الوطني للضمان الاجتماعي (CNAS) بمدينة المسيلة
أطروحة دكتوراه تخصص علم الإجتماع في العلوم الاجتماعية و الإنسانية
Keywords: الصحة التنظيمية - المواطنة التنظيمية; Organizational Health- Organizational Citizenship